Europe’s Large-Scale Land Acquisitions and Bibliometric Analysis - Marii Rasva; Evelin Jürgenson (Agriculture, 2022)
The agricultural sector in the European Union is largely characterized by a declining number of farms and an increasing size of surviving farms. The land is concentrating under the usage of fewer large agricultural producers. Meanwhile, a broad distribution of land ownership is the basis for the welfare of local economies and rural communities. Land distribution is one important component that guarantees our right to food, human rights, and sustainability in agriculture. The aim of this paper was to compile a systematic review of the existing literature on large-scale land acquisitions in Europe. The results are based on two different search methods. Firstly, documents and articles on large-scale land acquisitions were studied and, secondly, keyword research from the SCOPUS database and analysis using VOSviewer where performed. This study shows that large-scale land acquisitions are closely related to food security, human rights, global governance and international law, land tenure, biofuel production, and financialization through European Union common agricultural policy subsidies and foreign direct investments.